Differential Preincubation Effects of Nicardipine on OATP1B1- and OATP1B3-Mediated Transport in the Presence and Absence of Protein: Implications in Assessing OATP1B1- and OATP1B3-Mediated Drug-Drug Interactions - Ruhul Kayesh; Vishakha Tambe; Chao Xu; Wei Yue (MDPI AG, 2023)
Impaired transport activity of hepatic OATP1B1 and OATP1B3 due to drug-drug interactions (DDIs) often leads to increased systemic exposure to substrate drugs (e.g., lipid-lowering statins). Since dyslipidemia and hypertension frequently coexist, statins are often concurrently used with antihypertensives, including calcium channel blockers (CCBs). OATP1B1/1B3-related DDIs in humans have been reported for several CCBs. To date, the OATP1B1/1B3-mediated DDI potential of CCB nicardipine has not been assessed. The current study was designed to assess the OATP1B1- and OATP1B3-mediated DDI potential of nicardipine using the R-value model, following the US-FDA guidance. IC50 values of nicardipine against OATP1B1 and OATP1B3 were determined in transporter-overexpressing human embryonic kidney 293 cells using [3H]-estradiol 17β-D-glucuronide and [3H]-cholecystokinin-8 as substrates, respectively, with or without nicardipine-preincubation in protein-free Hanks' Balanced Salt Solution (HBSS) or in fetal bovine serum (FBS)-containing culture medium. Preincubation with nicardipine for 30 min in protein-free HBSS buffer produced lower IC50 and higher R-values for both OATP1B1 and OATP1B3 compared to in FBS-containing medium, yielding IC50 values of 0.98 and 1.63 µM and R-values of 1.4 and 1.3 for OATP1B1 and OATP1B3, respectively. The R-values were higher than the US-FDA cut-off value of 1.1, supporting that nicardipine has the potential to cause OATP1B1/3-mediated DDIs. Current studies provide insight into the consideration of optimal preincubation conditions when assessing the OATP1B1/3-mediated DDIs in vitro.